An optimal PMU placement method for power system observability under various contingencies - Abiri, Ebrahim; Rashidi, Farzan; Niknam, Taher (International transactions on electrical energy systems, 2015)
Summary In this paper, an efficient and comprehensive formulation for the optimal placement of phasor measurement units (PMUs) is proposed to minimize the number of PMU installation subject to full network observability. Moreover, the formulation is extended for assuring complete observability under single PMU loss or single line outage cases. Since the proposed optimization formulation is regarded to be a multiple‐solution one, both the installation cost and measurement redundancy are employed to differentiate the solutions with the same number of PMUs to be installed. In all of the investigations, the effect of zero‐injection buses in the power system is considered. The effectiveness of the proposed method is verified via some IEEE standard systems and compared with some newly reported methods. Results show that the proposed method is simple to implement and more accurate compared to other existing methods. Moreover, by considering the presented method, the minimum number of required PMUs is decreased in some cases. Copyright © 2014 John Wiley & Sons, Ltd.